MEMANFAATKAN WAKTU LUANG DENGAN BERWIRAUSAHA DI KELURAHAN BULUSAN KECAMATAN TEMBALANG KOTA SEMARANG - Nunik Kusnilawati; DC Kuswardani (Universitas YPPI Rembang, 2020)
AbstrakEntrepreneurship has become an alternative solution to employment problems and increased economic growth, so that various efforts have been made to create new entrepreneurs, includingthrough the development of an entrepreneurial spirit in all levels of society. Currently, entrepreneurshipsocialization is still needed, especially those targeting household-based potential community groupswhose entrepreneurial awareness levels are still relatively low. This community service activity in theform of entrepreneurship socialization was carried out in Bulusan Village, Tembalang District, SemarangCity with participants from PKK / housewives. The target of this activity is to instill an entrepreneurialspirit and increase knowledge about the techniques of starting a home business, in order to takeadvantage of free time. It is recommended that community service activities with the topic ofentrepreneurship be sustainable so that the household business can be realized so that it can increasefamily income / income..